FAMILY WITH CHILDREN IN TIMES OF PANDEMIC – WHAT, WHERE, HOW? DILEMMAS OF ADULT-IMPOSED PROHIBITIONS AND ORDERS - MARKOWSKA-MANISTA, URSZULA; ZAKRZEWSKA-OLĘDZKA, DOMINIKA (Society Register, 2020)
The coronavirus has closed adults and children at home. We communicate by phone or the Internet. Life has moved online, it has lost its rhythm within traditional systems of school and work. As a result of the COVID-19 pandemic spreading around the globe, many states have introduced numerous limitations in adults’ and children’s social functioning. The majority of education and care institutions have been closed, while companies and institutions whose type of activity allows to do so have decided to transform their work patterns into remote work. This new situation has particularly affected children, who, for their own and their families’ safety, have been cut off from the possibility to participate in activities and events that used to be part of their daily lives. In order to look at this situation and analyse the situation of families with children, an online survey questionnaire was conducted among 158 adults that aimed to collect data from below (from the perspective of reflexive adults looking after children in the situation of spatial-mobile limitations). In the article, we discuss changes in parents’ and children’s lives and analyse the social background of the areas discussed.